2022
DOI: 10.30997/almujtamae.v2i1.5442
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Akad Muzara’ah Dalam Meningkatkan Pendapatan Buruh Tani Di Desa Sukaharja

Abstract: Buruh tani di Desa Sukaharja Kecamatan Cijeruk Kabupaten Bogor memiliki beberapa kelemahan diantaranya adalah rendahnya tingkat pendapatan, bekerja musiman, terbatasnya lahan garapan dan memiliki keahlian yang terbatas hanya dibidang pertanian.  Hal ini menyebabkan  kondisi perekonomian rumah tangga buruh tani cenderung berada didalam lingkaran kemiskinan. Tujuan kegiatan pengabdian kepada masyarakat ini adalah untuk meningkatkan pendapatan buruh tani dengan menggunakan akad muzara'ah yang meningkatkan intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, in the research conducted by Kurnia and Imam, they found that the multilevel muzara'ah model was carried out between three parties, namely land owners, fund owners, and farm workers. At the first level, the fund owner enters into a muzara'ah contract with the land owner with a profit-sharing-based profit sharing scheme with a profit-sharing ratio of 60:40, which is 60 percent for fund owners and 40 percent for land owners (Kurnia & Aziz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the research conducted by Kurnia and Imam, they found that the multilevel muzara'ah model was carried out between three parties, namely land owners, fund owners, and farm workers. At the first level, the fund owner enters into a muzara'ah contract with the land owner with a profit-sharing-based profit sharing scheme with a profit-sharing ratio of 60:40, which is 60 percent for fund owners and 40 percent for land owners (Kurnia & Aziz, 2022).…”
Section: Introductionmentioning
confidence: 99%